2012
DOI: 10.1080/03057240.2012.656367
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning about family honour among two generations of Hindu Indian-Americans

Abstract: To investigate reasoning about family honour, 128 first generation (mean age = 27.2 years) and second generation Hindu Indian-American adults (mean age = 24.7 years) were presented hypothetical scenarios in which male or female protagonists defied common Hindu customs (e.g., arranged marriage, intra-religion marriage and premarital sexual abstinence). Questions assessed beliefs about customs, connections to family honour and socio-moral orientations towards honour violations. Both generations perceived intra-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, ethnic identification could not explain differences between the ethnic groups in the attitudes toward parental control of mate choice, and only among the Hindustani was ethnic identification associated with a positive attitude toward parental control, showing that in this group, the notion of being a Hindustani may foster the willingness to accept that parents control with whom their children marry (cf. Kay, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ethnic identification could not explain differences between the ethnic groups in the attitudes toward parental control of mate choice, and only among the Hindustani was ethnic identification associated with a positive attitude toward parental control, showing that in this group, the notion of being a Hindustani may foster the willingness to accept that parents control with whom their children marry (cf. Kay, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study in Mauritius, it was found that, especially among Hindus, and to a lesser extent among Muslims, the higher the ethnic identification, the lower the willingness to marry someone from another ethnic group (Ng Tseung-Wong & Verkuyten, 2015). Especially relevant in the present context, a study among young Hindu immigrants in the United States showed that intra-religion marriage was considered very important for group identity-related reasons, such as preserving Hindu culture and maintaining Hindu identity (Kay, 2012). We did not have specific predictions about differences between the ethnic groups in ethnic identification, but, as the main function of parental control is fostering in-group marriages, we expected that, overall, a positive attitude toward parental control of mate choice would be higher, the stronger the ethnic identification.…”
Section: Ethnic Identificationmentioning
confidence: 99%
“…Contextual factors have strong influence on parents' decisions to arrange marriages for their under-legal-age daughters. Arranged marriages and taboos on sexual practices before marriage are rituals and practices used to produce solidarity and uphold the identity and purity of the group (Kay, 2012). Another reason many parents are desirous for CM is the younger the wife-to-be the easier to socialize her as a servant in the husband's family home (Khan, Lurhathaiopath, & Matsushita, 2017;Yolah, 2001).…”
Section: Contextual Factors Contributing To the Practice Of Child Marriagementioning
confidence: 99%
“…These societies have a culturally embedded gender bias. The FH context helps to explain how the practice of CM serves the families in these areas and to explain variations in the educational outcomes and wellbeing of girls effected by the practice (Kay, 2012). This is consistent with Raj (2010), who reported, "…the primary contextual factor heightening risk for girl child marriage is gender inequity, often characteri[z]ed, at least in part, by lower access to education and employment opportunities for females relative to males" (p. 931).…”
Section: Family Honor and Child Marriagementioning
confidence: 99%
See 1 more Smart Citation